2021
DOI: 10.3389/fcell.2021.757445
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Chromosome Dynamics in Zebrafish

Abstract: Recent studies in zebrafish have revealed key features of meiotic chromosome dynamics, including clustering of telomeres in the bouquet configuration, biogenesis of chromosome axis structures, and the assembly and disassembly of the synaptonemal complex that aligns homologs end-to-end. The telomere bouquet stage is especially pronounced in zebrafish meiosis and sub-telomeric regions play key roles in mediating pairing and homologous recombination. In this review, we discuss the temporal progression of these ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 178 publications
2
14
0
Order By: Relevance
“…Cluster #2 includes genes that are specifically enriched in Symbrk and Nuc stages. Functionally enriched terms in this cluster included meiotic processes such as homologous recombination and mismatch repair ( Figure 2B ), consistent with the included leptotene-pachytene prophase oocytes in this sample, when DNA double-strand breaks are repaired through homologous recombination, as well as nonhomologous repair mechanisms ( Imai et al, 2021 ). Interestingly, enriched terms also included RNA transport and translation ( Figure 2B ), which are consistent with oocyte symmetry breaking and polarization of localized mRNA through Bb formation at these stages.…”
Section: Resultssupporting
confidence: 73%
“…Cluster #2 includes genes that are specifically enriched in Symbrk and Nuc stages. Functionally enriched terms in this cluster included meiotic processes such as homologous recombination and mismatch repair ( Figure 2B ), consistent with the included leptotene-pachytene prophase oocytes in this sample, when DNA double-strand breaks are repaired through homologous recombination, as well as nonhomologous repair mechanisms ( Imai et al, 2021 ). Interestingly, enriched terms also included RNA transport and translation ( Figure 2B ), which are consistent with oocyte symmetry breaking and polarization of localized mRNA through Bb formation at these stages.…”
Section: Resultssupporting
confidence: 73%
“…This was coupled with the formation of DSBs (Zickler and Kleckner, 2015). In our target reptiles, chromosome axes were detected as short stretches of SYCP3 and SYCP1 signal adjacent to the telomes, mirroring the patterns previously described in zebrafish (Blokhina et al, 2019;Imai et al, 2021). Moreover, telomeres clustered to one side of the nucleus forming the bouquet, presumably promoting homologous pairing and synapsis.…”
Section: Meiosis Progression Is Highly Conserved In Reptilessupporting
confidence: 78%
“…It is not until pachytene that chromosomes are completely synapsed and COs are resolved as chiasmata (the points where genetic material is actually exchanged). The mechanisms underlying meiotic progression have been extensively studied in several model organisms, including yeast, fruit flies, nematodes, mice and zebrafish ( Zickler and Kleckner, 2015 ; Blokhina et al, 2019 ; Imai et al, 2021 ). However, our understanding of the dynamics of meiotic prophase I and recombination among non-mammalian amniote vertebrates (i.e., sauropsids–birds/reptiles) remains incomplete ( Segura et al, 2013 ; Marín-Gual et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this section, the different subtypes of SPC during meiosis I were staged according to the previous article (Imai et al, 2021). Sycp3 was found with unique expression pattern in different subtypes of SPC-I.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dynamic expression pattern of Pcna during meiosis is still missing. In this study, we carefully characterized the expression dynamic of Pcna during meiosis I in zebrafish, and found that Pcna was polarly localized in the nucleus of leptotene SPC-I just underneath the Sycp3, suggesting a potential role of Pcna during the initiation of meiotic recombination when Sycp3 was shown adjacent to the telomeres (Imai et al, 2021). During the leptotene stage, telomeres moved to one pole of the nucleus where Sycp3 aggregated and the accumulated (Saito et al, 2014).…”
Section: Discussionmentioning
confidence: 99%